Nanoemulsion loaded with palm vitamin E for cosmeceutical applications / Tommy Julianto Bustami Effendi - Bustami Effendi, Tommy Julianto (Institute of Graduate Studies, UiTM, 2014)
Nanoemulsion is one of the alternative nano-lipid delivery systems of lipophilic active ingredients into the human skin in pharmaceutical and cosmetic applications. Palm vitamin E extract is a natural lipophilic active that contains α-, β-, δ-, γ-tocotrienols and α-tocopherol. Palm vitamin E has the potency as an antioxidant for delaying the skin ageing process in cosmetic application, although the skin absorption of palm vitamin E in conventional formulations is considered low. The high lipophilicity of palm vitamin E isomers causes the limitation in the skin permeation. The skin penetration can be enhanced by the loading of palm vitamin E extract in an oil phase of a nanolipid-delivery system such as nanoemulsion. Therefore, the potency of nanoemulsion loaded with palm vitamin E extract was studied.